2017
DOI: 10.1088/1361-6528/aa9533
|View full text |Cite
|
Sign up to set email alerts
|

In situpassivation of GaAsP nanowires

Abstract: We report on the structural and optical properties of GaAsP nanowires (NWs) grown by molecular-beam epitaxy. By adjusting the alloy composition in the NWs, the transition energy was tuned to the optimal value required for tandem III-V/silicon solar cells. We discovered that an unintentional shell was also formed during the GaAsP NW growth. The NW surface was passivated by an in situ deposition of a radial Ga(As)P shell. Different shell compositions and thicknesses were investigated. We demonstrate that the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 48 publications
4
48
0
Order By: Relevance
“…Subsequently, we discuss the structural and optical properties of GaAsP/GaP core-shell NWs, and the origin of the double luminescence peak in these structures (section 3.2). where the droplet crystallization took place, shows a characteristic sequence of different crystal phases, which was reported in the literature 28 : starting with a pure ZB at the NW stem, the crystal first turns into a mixture of cubic and hexagonal phases, then to a pure wurtzite (WZ) phase and finally returns to a ZB phase at the topmost position. Detailed discussion about the crystal quality and crystal phase at different NW-heights can be found elsewhere.…”
Section: Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…Subsequently, we discuss the structural and optical properties of GaAsP/GaP core-shell NWs, and the origin of the double luminescence peak in these structures (section 3.2). where the droplet crystallization took place, shows a characteristic sequence of different crystal phases, which was reported in the literature 28 : starting with a pure ZB at the NW stem, the crystal first turns into a mixture of cubic and hexagonal phases, then to a pure wurtzite (WZ) phase and finally returns to a ZB phase at the topmost position. Detailed discussion about the crystal quality and crystal phase at different NW-heights can be found elsewhere.…”
Section: Resultsmentioning
confidence: 59%
“…In our previous study on GaP passivated GaAsP NWs, we observed reproducibly an unintentional GaAsP shell with a lower P content just under the final GaP shell. 28 To determine at which growth stage this unintentional shell is formed and how it affects the light emission from the NWs, we first characterize the structure and the luminescence of GaAsP NWs without the GaP passivating shell (section 3.1). Subsequently, we discuss the structural and optical properties of GaAsP/GaP core-shell NWs, and the origin of the double luminescence peak in these structures (section 3.2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations